Analisis Potensi Ekonomi dan Daya Dukung Sosial Budaya Bambu - Joanetty Maria Annisa Dellty Nahak; Wilhelmina Seran; Ludji Michael Riwu Kaho (Wana Lestari, 2025)
This research aims to determine the use of bamboo plants by the Kateri Village community regarding the economic potential and socio-cultural supporting capacity of the Kateri Village community. The type of research used in this research is field research or qualitative descriptive. The data collection techniques used were vegetation analysis, bamboo plant identification, interviews, observation and documentation. The research results show that there are three types of bamboo plants, namely aur bamboo, betung bamboo and wuluh bamboo. The use of bamboo plants which have economic potential by the community has not had much of an impact on the community's economy, this is because the price of bamboo sold perlonjor is priced at IDR 5,000, and bamboo shoots IDR 15,000 and basically the use of bamboo plants used by the community is only to meet daily living needs. -day. The use of bamboo plants has provided socio-cultural support for village communities which has been inherited since ancient times and has a very important role in the social and cultural life of the community, where village communities use bamboo as a traditional Rama moruk weapon (poisonous arrows) and as a weaving tool, ladders. bamboo (Odam), a place for storing palm wine, making bebak for house walls, torches and traditional musical instruments as well as seating mats/bale-bale, simple stages, tents, fences, building construction, bridges, seats and tables. The use of bamboo by the village community is a habit inherited from their ancestors and is carried out continuously to this day.